Repartindo as águas do nordeste semiárido: uma análise comparativa dos modelos de alocação de água adotados no Ceará, Paraíba e Rio Grande do Norte - Sales, Clara de Assis Jerônimo (2013)
The discussions around the use of water as well as the society - nature relationship has become a vector of studies over the past two decades that aims to deepen discussions on the sustainability of the planet and minimize shortage problems faced by the pr oductive sector and the populations, putting this thread in politics played by public authorities, by users and by civil society organizations in the management of water in watersheds. Discuss the use and establish institutional arrangements that provide a more equitable distribution among users and planning current and future use and avoiding shortages still minimizing conflicts arising from this competition is the end of the water allocation. Brazil itself has the largest watershed in the world ( Amazon as‟ river ) and have one of the largest global water potential (14 % of all fresh water in the world), also suffers from a shortage, especially in semiarid northeast, which is contained in second most populated region in the country and has the least amount of fresh water available, that shortage is exacerbated by physical and climatic characteristics and misuse of water resources. The work presented here aims to develop a discussion of water management regarding its allocation in the Brazilian semiarid region, focusing primarily on the legal and institutional arrangements developed in three northeastern states: Ceará, Paraíba and Rio Grande do Norte and understanding that the appearance of this type of environmental planning in the region in the mid - '90s led to the development of shared and participatory water management.